Ethnic identity and scholastic effort: a multifaceted approach - Giuseppina Autiero (IZA Journal of Development and Migration, 2017)
When one analyses the influence of social identity on scholastic effort, ethnic identity largely contributes to determine it. In this paper, ethnic identity is meant as the attachment to one's cultural heritage and the adaptation to host societies; this allows considering how conflicting demands and social pressure from parents, peers, ethnic community and host societies influence children's effort. Attention is also paid to the locus of control; thereby, the effects of the interaction between the social contex-ethnic identity-and personal traits such as the locus of control are considered. The analysis is developed through a theoretical model whose results partly show that children's effort may be influenced positively by parents with strong attitudes towards adaptation and negatively by their peers in school who belong to marginalized groups vulnerable to discrimination and convinced that school does not improve one's socio-economic status. Nevertheless, the drawbacks of the social context can be counterbalanced by a strong locus of control.
Keywords: I20; I29; Z10; 330; Scholastic effort; Ethnic identity; Personal identity